Impacts of human papillomavirus vaccination for different populations: A modeling study. Issue 5 (16th April 2018) - Baussano, Iacopo; Lazzarato, Fulvio; Ronco, Guglielmo; Franceschi, Silvia
Abstract : International variations in the prevalence of HPV infection derive from differences in sexual behaviors, which are also a key factor of the basic reproductive number ( R0 ) of HPV infection in different populations. R 0 affects the strength of herd protection and hence the impact of a vaccination program. Similar vaccination programs may therefore generate different levels of impact depending upon the population's pre‐vaccination HPV prevalence. We used IARC's transmission model to estimate ( i ) the overall effectiveness of vaccination versus no vaccination in women aged 15–34 years measured as percent prevalence reduction (%PR) of HPV16 and ( ii ) the corresponding herd protection in populations with gender‐equal or traditional sexual behavior and with different levels of sexual activity, corresponding to pre‐vaccination HPV16 prevalence from 1 to 8% as observed worldwide. Between populations with different levels of gender‐equal sexual activity, the highest difference in %PR under girls‐only vaccination is observed at 40% coverage (91%PR vs . 48%PR for 1% and 8% pre‐vaccination prevalence, respectively). HPV16 elimination is obtained with 55 and 97% coverage, respectively. To achieve desirable levels of HPV16 prevalence after vaccination, different levels of coverage are required in populations with different levels of pre‐vaccination HPV16 prevalence, for example, in populations with gender‐equal sexual behavior a decrease to 1/1000 HPV16 from pre‐vaccination prevalence of 1 and 8% would require coverages of 37 and 96%, respectively. In traditional populations, corresponding coverages would need to be 28 and 93%, respectively. In conclusion, pre‐vaccination HPV prevalence strongly influences herd immunity and helps predict the overall effectiveness of HPV vaccination. Abstract : What's new? Differences in sexual activity from one population to another account for up to a ten‐fold difference in HPV prevalence, which in turn affects cervical‐cancer risk. How do these factors impact the effectiveness of HPV‐vaccination programs? In this epidemiological study, the authors found that, in countries where sexual behavior is based on traditional norms and HPV prevalence remains low, an early introduction of HPV vaccination will anticipate any increase of HPV prevalence among young women due to the liberalization of social attitudes.